Statin Pretreatment and Microembolic Signals in Large Artery Atherosclerosis: A Systematic Review and Meta-Analysis. Issue 8 (August 2018) - Safouris, Apostolos; Katsanos, Aristeidis H.; Kerasnoudis, Antonios; Krogias, Christos; Kinsella, Justin A.; Sztajzel, Roman; Lambadiari, Vaia; Deftereos, Spyridon; Kargiotis, Odysseas; Sharma, Vijay K.; Demchuk, Andrew M.; Saqqur, Maher; et al.
Abstract : Background and Purpose—: Scarce data indicate that statin pretreatment (SP) in patients with acute cerebral ischemia because of large artery atherosclerosis may be related to lower risk of recurrent stroke because of a decreased incidence of microembolic signals (MES) during transcranial Doppler monitoring. Methods—: We performed a systematic review and meta-analysis of available observational studies reporting MES presence/absence or MES burden, categorized according to SP status, in patients with acute cerebral ischemia because of symptomatic (≥50%) large artery atherosclerosis. In studies with partially-published data, authors were contacted for previously unpublished information. We also performed a sensitivity analysis of studies with data on MES burden categorized according to SP status, and an additional subgroup analysis in patients receiving higher-dose SP (atorvastatin 80 mg or rosuvastatin 40 mg daily). Results—: Seven eligible study protocols were identified (610 patients, 54% with SP). SP was associated with a reduced risk of MES detection during transcranial Doppler monitoring (risk ratio=0.67; 95% CI, 0.45–0.98), with substantial heterogeneity between studies ( I 2 =52%). In studies reporting MES burden (n=4), a significantly lower number of MES were identified in patients with compared with those without SP (mean difference=−0.92; 95% CI, −1.64 to –0.19), with no evidence of heterogeneity between studies ( I 2 =49%). Subgroup analysis revealed that higher-dose SP reduced the risk of detecting MES (risk ratio=0.23; 95% CI, 0.06–0.88), with no evidence of heterogeneity between studies ( I 2 =0%). Conclusions—: SP seems to be associated with a lower incidence and burden of MES in patients with acute cerebral ischemia because of large artery atherosclerosis. Abstract : Supplemental Digital Content is available in the text.